Element Composition and Toxicity of Seaweed Algae (Ulva lactuca, Laurencia obtuse and Padina pavonica) Toward Shrimp - Ahmed Muhammad; Ibrahim Hassan; Manar Tawfeek; Hayam Ahmed Ibrahim (Arab Universities Journal of Agricultural Sciences, 2022)
This study examined the macro and trace element contents as well as the cytotoxicity of Laurencia obtusa, Ulva lactuca, and Padina pavonica algae collected from the Mediterranean coast of Egypt (Alexandria coast). The results indicated that the seaweed samples contained high concentrations of Ca, Cl, Mg, K, Na, P and Fe. The Cu and Zn contents of the algae were in the ranges of 0.39-0.95 mg/100 g dw and 0.11-0.49 mg/100 g dw respectively. Fresh red algae contained the highest level of Zn and Cu, whereas the iodine level was 1.52, 1.27 and 1.01 mg/100g in fresh each of Padina pavonica, Laurencia obtuse and Ulva lactuca respectively. Fresh red, fresh green, dry green, dry red, in addition to fresh and dried brown algae had maximum lead (Pb) levels of 0.16, 0.14, 0.13, 0.12, 0.04 and 0.02 g/100 g respectively. Fresh red algae contained the highest Cd and Mn levels, whereas dried brown algae exhibited the lowest Cd and Mn concentrations. Different extracts of fresh and dried brown algae exhibited significant larvicidal activity against brine shrimp. LC50 values indicated that dry samples were more cytotoxic than fresh samples.